'Linguistically Wounded': Veronica Forrest-Thomson, Sylvia Plath, and the Limits of Poetic Artifice. Issue 1 (10th September 2018) - Moser, Anna
Abstract : Based on the archival evidence of Veronica Forrest-Thomson's annotations to Sylvia Plath's 1971 collection Winter Trees, as well as a 1972 typescript of Forrest-Thomson's review of Winter Trees, which she never published, this article argues that Forrest-Thomson's engagement with Plath's late poetry played a crucial role in the development of her theory of 'poetic artifice'. Yet I contend that the poems of Winter Trees by no means offer themselves as self-evident exemplars of such a theory, and I explore this disjunction by juxtaposing Forrest-Thomson's revisionary account of Plath in Poetic Artifice: A Theory of Twentieth-Century Poetry, which posits the poems 'Daddy' and 'Purdah' as anti-confessional works of art that clearly indicate their own 'unreality', against the Winter Trees review, which is more critical of Plath's 'compromises'. Because Forrest-Thomson's aesthetic project is further complicated by her own development as a poet, I also consider a selection of poems published in the 1974 Omens Poetry Pamphlet Cordelia: or 'A poem should not mean but be', in order to explore an elided, yet suggestive, relation between feeling and theory in her poetry. Finally, I argue that this relation, which Plath's 'Purdah' would seem to both prefigure and sanction, signals the presence of a reticent 'linguistic emotionality' in Forrest-Thomson's work that not only contests the authority of her male modernist models, but also anticipates contemporary critical discourses in experimental poetry and poetics.